Association and Pathways between Dietary Manganese Intake and Incident Venous Thromboembolism - Huang, Yu; Zhang, Yanjun; Yang, Sisi; Xiang, Hao; Zhou, Chun; Ye, Ziliang; Liu, Mengyi; He, Panpan; Zhang, Yuanyuan; Gan, Xiaoqin; Qin, Xianhui (Thrombosis and Haemostasis, 2023)
Background The association between dietary manganese (Mn) intake and the risk of venous thromboembolism (VTE) remains unknown. We aimed to investigate the associations of dietary Mn intake with incident VTE, and the underlying mediating roles of obesity markers (body mass index [BMI] and waist circumference), hemorheological parameters (red cell distribution width [RDW], platelet count [PLT], and mean platelet volume [MPV]), and inflammatory biomarkers (C-reactive protein [CRP] and white blood cell count [WBC]) in this association.Methods A total of 202,507 adults from the UK Biobank with complete dietary data and without VTE at baseline were included. Dietary information was collected by the online 24-hour diet recall questionnaires (Oxford WebQ). The primary outcome was incident VTE, a composite of incident deep vein thrombosis (DVT) and pulmonary embolism (PE).Results During a median follow-up of 11.6 years, 4,750 participants developed incident VTE. Overall, there were significantly inverse relationships of dietary Mn intake with incident VTE (per 1 mg/day increment; adjusted hazard ratio [HR]: 0.92; 95% confidence interval [CI]: 0.90–0.95), incident DVT (per 1 mg/day increment; adjusted HR: 0.93; 95% CI: 0. 90–0.96), and incident PE (per 1 mg/day increment; adjusted HR: 0.91; 95% CI: 0.88–0.95). BMI, waist circumference, RDW, CRP, and WBC significantly mediated the association between dietary Mn intake and incident VTE, with the mediated proportions of 36.0, 36.5, 4.2, 4.3, and 1.6%, respectively. However, MPV and PLT did not significantly mediate the association.Conclusion Our study shows that dietary Mn intake was inversely associated with incident VTE. The inverse association was mainly mediated by obesity, followed by inflammatory biomarkers and RDW. Our findings are just hypothesis-generating, and further confirmation of our findings in more studies is essential.
Keywords: dietary manganese; venous thromboembolism; obesity; red cell distribution width; inflammation